2019
DOI: 10.1186/s12936-019-2829-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the residual efficacy of indoor residual spraying with bendiocarb (FICAM WP 80) in six health districts in Senegal

Abstract: Background From 2011 to 2014, an indoor residual spray (IRS) programme for malaria vectors control was implemented in six health districts in Senegal. The main objective of the present study was to evaluate the efficacy of bendiocarb (FICAM WP 80) sprayed on different wall surfaces and its impact on malaria vectors. The entomological monitoring activities were carried out monthly in five treated sentinel villages and one control untreated village in each district. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Given the measured over-application of formulation to the surfaces measured by HPLC, the concentration required in any final IRS formulation would require further investigation. The known challenges of achieving long-lasting residual efficacy on a relatively uneven and porous mud surface (for example [ 23 , 24 ]) was again observed and will need to be a consideration in developing a final IRS formulation. Even though a preliminary prototype IRS formulation of Tenebenal™ was used to measure residual efficacy, it performed well compared to existing IRS products applied at their recommended application rate.…”
Section: Discussionmentioning
confidence: 99%
“…Given the measured over-application of formulation to the surfaces measured by HPLC, the concentration required in any final IRS formulation would require further investigation. The known challenges of achieving long-lasting residual efficacy on a relatively uneven and porous mud surface (for example [ 23 , 24 ]) was again observed and will need to be a consideration in developing a final IRS formulation. Even though a preliminary prototype IRS formulation of Tenebenal™ was used to measure residual efficacy, it performed well compared to existing IRS products applied at their recommended application rate.…”
Section: Discussionmentioning
confidence: 99%
“…IRS has been conducted with different pyrethroids and formulations between 2007 and 2011. The NMCP shifted to bendiocarb from 2011 to 2014, then to organophosphate between 2014 and 2017 [ 22 ]. However, no IRS was conducted in 2018 due to the decision of the PMI to stop the program in Senegal [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NMCP shifted to bendiocarb from 2011 to 2014, then to organophosphate between 2014 and 2017 [ 22 ]. However, no IRS was conducted in 2018 due to the decision of the PMI to stop the program in Senegal [ 22 ]. All these insecticide management strategies may have contributed to the reduction in the pyrethroids selection pressure and thus the frequency of Vgsc-1014F mutation in the local vector populations [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation study summarised that changes in concentration of insecticide and surface type (shaded and unshaded) effected wood more than concrete in relation to the effectiveness of the insecticide and this is most likely could be due to surface porosity. According to Lo et al, [15] high porosity of a wall structure could influence the efficacy of insecticides sprayed. His study demonstrated that mud wall has better insecticide efficacy compared to cement wall.…”
Section: Bio Efficacy Of the Insecticidementioning
confidence: 99%